Children's experiences and feelings in a selected evacuation center in Marikina City - Borines, Maria Talitha Estrella L.
This study was done to describe children's experiences and feelings in an evacuation center. The participants were six-to-eight-year- old children of Barangay Tumana who frequently stay in evacuation centers in an event of a flood. The participants were asked to draw their experiences while they were inside the evacuation center. The participants were asked to say something about their drawings and were interviewed regarding their feelings during their stay in the evacuation center and what they expect to see in an evacuation center to make their stay comfortable, happy, and meaningful. For each response category, a frequency count was carried out. A total of six categories emerged for children's experiences namely, sensory experiences, bio-physical experiences, family related experiences, social activities, and rules imposed by parents. A total of seven categories arose for children's feelings with fear as the theme to generate the highest response. These categories were as follows: afraid, happy, sad, pity, having a difficult time, frustrated, and happy. In response to their experiences and feelings, it was observed that children were able to express what they expect to see in an evacuation center to make their stay comfortable, happy, and meaningful during the difficult times brought about by the flood. Two categories were generated on what children expect to see in an evacuation center which were grouped as material things and social relationships. This study recommends the development of programs, interventions, designing of evacuation centers, and food planning for young children.